Intracellular distribution of nerve growth factor in rat pheochromocytoma PC12 cells: evidence for a perinuclear and intranuclear location. - Marchisio, P C (1980)
The distribution of nerve growth factor (NGF) in rat pheochromocytoma cells (clone PC12) has been studied with two different techniques: immunofluorescence and autoradiography. It was found that NGF is progressively internalized in the cytoplasmic compartment and eventually accumulates in the form of discrete dots around the nucleus. A fraction of the internalized NGF appears within the nucleoplasm, often contiguous with the nucleolus. It is suggested that cytoplasmic and perinuclear NGF may be be in contact with a pool of tubulin or actin-like proteins in their soluble or organized form and play a key role in the process of arrest of division and neurite growth.